2023
DOI: 10.1007/s13402-023-00786-w
|View full text |Cite
|
Sign up to set email alerts
|

Small extracellular vesicles promote invadopodia activity in glioblastoma cells in a therapy-dependent manner

Abstract: Purpose The therapeutic efficacy of radiotherapy/temozolomide treatment for glioblastoma (GBM) is limited by the augmented invasiveness mediated by invadopodia activity of surviving GBM cells. As yet, however the underlying mechanisms remain poorly understood. Due to their ability to transport oncogenic material between cells, small extracellular vesicles (sEVs) have emerged as key mediators of tumour progression. We hypothesize that the sustained growth and invasion of cancer cells depends on bi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3
1
1

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 162 publications
2
2
0
Order By: Relevance
“…When these were compared against the MNG EV proteins we identified, a total of 11 common proteins were identified (PGK1, ALDOA, ANAXA1, HSPB1, PFN1, PKM, S100A11, SPTBN1, SPTAN1, PLEC and TF). Our study not only confirms the presence of proteins previously identified in MNG EVs (4,(7)(8)(9)(10)(11)(12)25), but also identified novel proteins that have not been previously reported in association with MNG EVs.…”
Section: Discussionsupporting
confidence: 89%
See 3 more Smart Citations
“…When these were compared against the MNG EV proteins we identified, a total of 11 common proteins were identified (PGK1, ALDOA, ANAXA1, HSPB1, PFN1, PKM, S100A11, SPTBN1, SPTAN1, PLEC and TF). Our study not only confirms the presence of proteins previously identified in MNG EVs (4,(7)(8)(9)(10)(11)(12)25), but also identified novel proteins that have not been previously reported in association with MNG EVs.…”
Section: Discussionsupporting
confidence: 89%
“…Differential expression analysis was utilized to reveal the relative abundance of proteins that were enriched in the EVs compared to the tumour tissue. Our study not only confirms the presence of proteins previously identified in GBM EVs from various sources (including CUSA washings, cell lines, and plasma) (4,(7)(8)(9)(10)(11)(12)25), but also crucially identified novel proteins that have not been reported before in association with GBM EVs before including proteins associated with solute carrier transporters and fatty acid transport. Recently it has been shown that solute carrier family members can promote the progression of GBM by activating the PI3-AKT signalling pathway (44).…”
Section: Discussionsupporting
confidence: 87%
See 2 more Smart Citations